Optimization and chemical demulsification of crude oil emulsions - Nuraini, Mansor (2012)
In this thesis, the potentials of traditional and environmentally friendly chemicals in demulsification of water-in-crude oil emulsions were investigated. The work began with some characterization studies to provide understandings of fundamental issues such as formation, formulation and breaking of emulsions by both conventional and environmentally friendly chemicals approaches. ASTM column separation was utilized for SARA-fractionation technique to characterize crude oil into saturates, aromatics, resins and asphaltenes compounds. The aim was to obtain an optimized operating condition as well as fundamental understanding of water-in-crude oil stability upon which further developments on demulsification processes could be developed. The stability studies were carried out by analyzing operating conditions such as emulsion processing time, droplet size, types and concentration of surfactants, water-oil ratio and stirring intensity. In the demulsification part, this study also investigated the performances of four functional groups of chemical demulsifiers which were amine, polyhydric alcohol, alcohol and biodegradable functional groups. For chemical screening, One Factor at A Time (OFAT) method adopted. Three crude oils namely, crude oil A, B, and C were utilized. These crude oils were obtained from Petronas Penapisan Melaka, Malaysia. Among of these oils, crude oil C was found to be the heaviest and best for stability and followed by crude oil B and A respectively. For chemical demulsifiers, results show that octylamine was the best for water separation (99 % at day-one) and followed by palm based oleyl amine (PBOA) (99 % at day- three), hexylamine (98 % at day-five) and coca amine (97.5 % at day-five). For optimization part, the response surface methodology (RSM) was utilized and results showed that the optimum conditions for each crude oil. The results obtained in this study have exposed the capability of chemicals (conventional and environmentally friendly) method in breaking of water-in-crude oil emulsion. Further works are nevertheless required to provide deeper understanding the mechanisms involved to facilitate the development of an optimum system applicable to the industry.